(untitled) (ModaPalavra e-periódico, 2015)
Considering the importance of establishing a relationship between design management and the process of product development, this paper presents a set of complementary tools, and his major contributions during the implementation of a fashion design process in a fashion female clothing MPE. It’s presented based on literature review and case study, the achieved result is instigated the importance of its dissemination through this article.